La “Chiesa domestica”: il coraggio del cammino. Note a margine alla Prefazione del cardinal Angelo Scola alla “Amoris Lætitia” - Pinna, Samuele (Alpha Omega, 2017)
Summary: Angelo Scola has devoted himself to a long and articulated preface to Pope Francis’ post-synodal apostolic exhortation on love in the family, Amoris Lætitia. In this contribution, it is intended to provide simple marginal notes to what Cardinal Scola writes, withoutwishing to exhaust the richness of what he has said, but seeking to develop the aspect of the ecclesial dimension, recalled in Amoris Lætitia and underlined in the Preface. In fact, Christian matrimony is “the reflection of the union between Christ and his Church and is realised fully in the union between a man and a woman who give themselves reciprocally in a love that is exclusive and in free fidelity, who belong to each other until death and who are open to thetransmission of life and who are consecrated by the sacrament which confers upon them the grace to establish themselves as a domestic church and as the ferment of new life for society” (n. 262).Key words: Amoris Lætitia, Church, Marriage, holiness, sin, love, indissolubility.Parole chiave: Amoris Lætitia, Chiesa, Matrimonio, santità, peccato, amore, indissolubilità.